Biostimulant Effects of Chaetomium globosum and Minimedusa polyspora Culture Filtrates on Cichorium intybus Plant: Growth Performance and Metabolomic Traits - Spinelli, Veronica; Brasili, Elisa; Sciubba, Fabio; Ceci, Andrea; Giampaoli, Ottavia; Miccheli, Alfredo; Pasqua, Gabriella; Persiani, Anna Maria (Frontiers in Plant Science, 2022)
In the present study we investigated the biostimulant effect of fungal culture filtrates obtained from Chaetomium globosum and Minimedusa polyspora on growth performance and metabolomic traits of Cichorium intybus plants. For the first time, we showed that M. polyspora culture filtrate exerts a direct plant-growth promoting effect, through an increase of biomass, both in shoots and roots, and of the leaf area. Conversely, no significant effect on morphological traits and biomass yield was observed in C. intybus plants treated with C. globosum culture filtrate. Based on 1H-NMR metabolomics data, differential metabolites and their related metabolic pathways were highlighted. The treatment with C. globosum and M. polyspora culture filtrates stimulated a common response in C. intybus roots involving the synthesis of 3-OH-butyrate through the decrease of the synthesis of fatty acids and sterols, as a mechanism balancing the NADPH/NADP+ ratio. The fungal culture filtrates differently triggered the phenylpropanoid pathway in C. intybus plants: C. globosum culture filtrate increased phenylalanine and chicoric acid in the roots, whereas M. polyspora culture stimulated an increase of 4-OH benzoate. Chicoric acid, whose biosynthetic pathway in chicory plant is putative and still not well known, is a very promising natural compound playing an important role in plant defence. On the other hands, benzoic acids serve as precursors for a wide variety of essential compounds playing crucial roles in plant fitness and defence response activation. To the best of our knowledge this is the first study that shows the biostimulant effect of C. globosum and M. polyspora culture filtrates on C. intybus growth and metabolome, increasing the knowledge on fungal bioresources for the development of biostimulants.